OCT-detected optic nerve head neural canal direction, obliqueness, and minimum cross-sectional area in healthy eyes - Hong, Seungwoo; Scheuerle, Alexander F. (American journal of ophthalmology, 2019)
Purpose - To assess anterior scleral canal opening (ASCO) offset relative to Bruch's membrane opening (BMO) (ASCO/BMO offset) so as to determine neural canal direction, obliqueness, and minimum cross-sectional area (NCMCA) in 362 healthy eyes. - Design - Cross-sectional study. - Methods - After optical coherence tomography optic nerve head and retinal nerve fiber layer thickness (RNFLT) imaging, BMO and ASCO were manually segmented. Planes, centroids, size, and shape were calculated. Neural canal direction was defined by projecting the neural canal axis vector (connecting BMO and ASCO centroids) onto the BMO plane. Neural canal obliqueness was defined by the angle between the neural canal axis and the BMO plane perpendicular vector. NCMCA was defined by projecting BMO and ASCO points onto a neural canal axis perpendicular plane and measuring the area of overlap. The angular distance between superior and inferior peak RNFLT was measured, and correlations between RFNLT, BMO, ASCO, ASCO/BMO offset, and NCMCA were assessed. - Results - Mean (SD) NCMCA was significantly smaller than either the BMO or ASCO area (1.33 (0.42), 1.82 (0.38), 2.22 (0.43) mm2, respectively), and most closely correlated to RNFLT (P < .001, R2 = 0.158). Neural canal direction was most commonly superior-nasal (55%). Mean neural canal obliqueness was 39.4° (17.3°). The angular distance between superior and inferior peak RNFLT correlated to neural canal direction (P ≤ .008, R2 = 0.093). - Conclusions - ASCO/BMO offset underlies neural canal direction, obliqueness, and NCMCA. RNFLT is more strongly correlated to NCMCA than to BMO or ASCO, and its peripapillary distribution is influenced by neural canal direction.